Seeds for Needs - India: Broadening the genetic base of crops to empower farmers for climate change adaptation through crowdsourcing - Mittra, S.; Mathur, P.N.; Dadlani, M.; Gupta, A. (Bioversity International, 2015)
A poster to introduce our approach to exposing farmers to more crops and their varieties, increasing first-hand knowledge about different traits and strengthening their seed systems and seed saving capacity. The poster shows how we are upscaling activities and some of the results so far, as well as innovative weather capturing technologies we are using and future plans.